2023
DOI: 10.1042/cs20220300
|View full text |Cite
|
Sign up to set email alerts
|

Circulating biomarkers associated with placental dysfunction and their utility for predicting fetal growth restriction

Abstract: Fetal growth restriction (FGR) leading to low birth weight (LBW) is a major cause of neonatal morbidity and mortality worldwide. Normal placental development involves a series of highly regulated processes involving a multitude of hormones, transcription factors, and cell lineages. Failure to achieve this leads to placental dysfunction and related placental diseases such as pre-clampsia and FGR. Early recognition of at-risk pregnancies is important because careful maternal and fetal surveillance can potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 172 publications
0
6
0
Order By: Relevance
“…Defective deep placentation has now been established to be strongly associated with the pathogenesis of the obstetric syndromes 9 of pre‐eclampsia, FGR and PTB. Abnormalities in circulating levels of maternal PlGF and sFlt‐1 are strongly indicative, if not diagnostic, of placental dysfunction 17,18,49 , and have been incorporated into screening 5 and diagnostic tests 50 for suspected preterm pre‐eclampsia. In a recent cohort study 51 , maternal PlGF levels were found to decrease gradually as pregnancy progressed in women whose placenta was shown ultimately to have histological evidence of maternal vascular malperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defective deep placentation has now been established to be strongly associated with the pathogenesis of the obstetric syndromes 9 of pre‐eclampsia, FGR and PTB. Abnormalities in circulating levels of maternal PlGF and sFlt‐1 are strongly indicative, if not diagnostic, of placental dysfunction 17,18,49 , and have been incorporated into screening 5 and diagnostic tests 50 for suspected preterm pre‐eclampsia. In a recent cohort study 51 , maternal PlGF levels were found to decrease gradually as pregnancy progressed in women whose placenta was shown ultimately to have histological evidence of maternal vascular malperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Placental dysfunction is associated with an imbalance in placentally derived pro-and anti-angiogenic factors. Low levels of placental growth factor (PlGF), a strongly proangiogenic hormone, and elevated levels of its antiangiogenic counterpart, soluble fms-like tyrosine kinase-1 (sFlt-1) 17,18 , as well as an increased sFlt-1/PlGF ratio are seen in women with pre-eclampsia and FGR, and are reflective of placental dysfunction 17,[19][20][21][22] . Although there is some evidence that maternal PlGF levels and the sFlt-1/PlGF ratio may be helpful in predicting timing of delivery and rate of disease progression in pregnancies complicated by FGR [23][24][25][26][27] , there are limited data regarding their association with, or potential for, prediction of PTB beyond their utility in screening 28,29 and diagnosis 30,31 of adverse outcome 24,32,33 in women with pre-eclampsia or FGR.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the “at risk” infant is however difficult. Although fetal size, reduced intrauterine growth velocity 8 , 45 and evidence of cerebral redistribution 32 , 46 , 47 are associated with greater odds of perinatal morbidity and mortality 8 , 45 , 48 , 49 , 50 other factors, such as placental derived biomarkers 51 may need to be considered. The use of iterative and automated artificial intelligence techniques currently evaluated in other areas of science and medicine 52 , 53 , 54 could be future strategies to identify pregnancies and infants at risk of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The development of defective deep placentation characterized by nontransformation of myometrial spiral arteries 10 , 11 leads to placental ischemia 9 , 12 and perturbations in levels of circulating angiogenic factors. 13 , 14 Low levels of placental growth factor (PlGF), a proangiogenic factor, and elevated levels of its antiangiogenic counterpart, soluble fms‐like tyrosine kinase‐1 (sFlt‐1), are reflective of placental stress and dysfunction. Both have been shown to be useful for screening 15 , 16 and prediction of adverse outcomes 17 , 18 , 19 , 20 in pregnancies complicated by FGR and pre‐eclampsia (PET).…”
Section: Introductionmentioning
confidence: 99%